Carpophilus hemipterus (Linnaeus, 1758) (Coleoptera, Nitidulidae), PRIMEIRO REGISTRO DE OCORRÊNCIA EM RAÇÃO CANINA NA REGIÃO DE VIÇOSA, MINAS GERAIS, BRASIL - Rodrigo de Oliveira Simões; Marco Aurélio Guerra Pimentel; Adalberto Hipólito Sousa; Lêda Rita D'Antonino Faroni; Juliana Cristina dos Santos (Revista Caatinga, 2008)
This paper reports the first occurrence of insect-pest Carpophilus hemipterus L. (Coleoptera: Nitidulidae) infesting dog food collected in Viçosa, Minas Gerais in the period may 2008.